TESTING AS THE BASIC TECHNOLOGY OF THE KNOWLEDGE CONTROL OF LISTENERS OF COURSE ECDL - Kravtsov, Г.М.; Sharko, В. Д. (Journal of Information Technologies in Education (ITE), 2010)
Results of research of distance testing systems and their introduction for the knowledge control in the course of professional skill improvement under program ECDL with use of distance learning are presented.